STUDY ON RESOURCE SCHDULING AND ALLOCATON FOR MULTI-OBJECTIVE-BASED VIRTUAL MACHINES. - KRISHNAKUMAR, K.; MALARVIZHI, N.; KUMANAN, T. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Over the Internet, the way of storing and access to data and programs is termed cloud computing. This does not require a dedicated server in residence. Cloud computing provisions data access anywhere, any time. Google Drive, Apple I Cloud, Amazon are some of the big retailers in Cloud. Users go on with pay and use service in Cloud. Many researchers have developed various meta-heuristic algorithms to optimize capital distribution of resources. The virtual resource allocation method includes construction/destruction of virtual machines dynamically, without affecting the execution of the application. Therefore, assigning resources at the virtual machine level provides several distinct advantages such as consistency in the distribution and migration of virtual resources. In this paper various reviews related to study on resource schduling and allocaton for multi-objective-based virtual machines has been studied.